Azacitidine‐associated haemorrhagic enteritis in a case of myelodysplastic syndrome: A case report. (20th May 2020) - Hagino, Takeshi; Shinomiya, Wataru; Hidai, Hiroko; Umeda, Miki; Kurimoto, Miwa; Saga, Reina; Tsutsumi, Hisashi; Shibata, Yoshiaki; Akiyama, Hideki; Motomura, Sayuri
Abstract: What is known and objective: 5‐Azacitidine (AZA) is an agent widely used to treat myelodysplastic syndrome (MDS). Case description: We herein report an 83‐year‐old woman diagnosed with MDS who was treated with AZA. She tolerated the first cycle of AZA; however, severe adverse events involving haemorrhagic enteritis with multiple intestinal ulcers developed after the second and third cycles. Additionally, the interval between the administration of AZA and the development of haematochezia shortened with each cycle of AZA. What is new and Conclusion: We herein report as‐yet‐undescribed potential side effects, AZA‐associated haemorrhagic enteritis that should be kept in mind.